Assessment of anticoccidial efficacy of novel Triazine compound and Sulfaclozine against experimentally induced caecal coccidiosis in broiler chickens - Hagag, Dina; El-Shazly, Kamal; Abd El-Aziz, Magdy; Abd El-Latif, Amira; El Sharkaway, Hanem; Abdo, Walied; Barakat, Mohamed (Penerbit Universiti Kebangsaan Malaysia, 2020)
This study was performed to investigate the theraputic efficacy of toltrazuril, sulfaclozine sodium and their combination in broiler chicken for the treatment of experimentally induced caecal coccidiosis. For this purpose, seventy-five day-old chicks were randomly divided into five equal groups (15 each). G1 , kept as control negative; G2 , infected non treated (control positive); G3 , infected treated with toltrazuril (1 mL/L); G4 , infected treated with sodium sulfaclozine (2 mL/L); G5 , infected treated with toltrazuril (1 mL/L) + sulfaclozine Na (2 g/L). All groups except negative control group were inoculated orally with 5 × 104 sporulated oocysts of Eimeria tenella (field isolate) on the day 15th of age. According to the present results, G2 showed a significant increase in oocyst count, AST, ALT, ALP, uric acid, and creatinine, with significant decrease in body weight gain, hematological parameters, total protein, and albumin. Treatment decreased the harmful effect of infection but some significant differences were shown between infected and treated groups and non infected and non treated group in assessment criteria. Furthermore, the histopathological findings were also discussed. In conclusion, the current study showed that the application of both tested drugs gave significant and satisfactory improvement in the assessment criteria as well as they are effective in control of coccidiosis caused by Eimeria tenella.